Enzymatic Switching Between Archaeal DNA Polymerases Facilitates Abasic Site Bypass - Feng, Xu; Zhang, Baochang; Xu, Ruyi; Gao, Zhe; Liu, Xiaotong; Yuan, Guanhua; Ishino, Sonoko; Feng, Mingxia; Shen, Yulong; Ishino, Yoshizumi; She, Qunxin (Frontiers in Microbiology, 2021)
Abasic sites are among the most abundant DNA lesions encountered by cells. Their replication requires actions of specialized DNA polymerases. Herein, two archaeal specialized DNA polymerases were examined for their capability to perform translesion DNA synthesis (TLS) on the lesion, including Sulfolobuss islandicus Dpo2 of B-family, and Dpo4 of Y-family. We found neither Dpo2 nor Dpo4 is efficient to complete abasic sites bypass alone, but their sequential actions promote lesion bypass. Enzyme kinetics studies further revealed that the Dpo4’s activity is significantly inhibited at +1 to +3 site past the lesion, at which Dpo2 efficiently extends the primer termini. Furthermore, their activities are inhibited upon synthesis of 5-6 nt TLS patches. Once handed over to Dpo1, these substrates basically inactivate its exonuclease, enabling the transition from proofreading to polymerization of the replicase. Collectively, by functioning as an “extender” to catalyze further DNA synthesis past the lesion, Dpo2 bridges the activity gap between Dpo4 and Dpo1 in the archaeal TLS process, thus achieving more efficient lesion bypass.